PRIMARY SCHOOL MATHEMATICS MOTIVATION SCALE - Ersoy, Ezgi; Oksuz, Cumali (European Scientific Journal, ESJ, 2015)
This study was aimed at developing a scale for determining motivation of primary school students towards learning Mathematics. A preliminary form of the scale included 74 Three-point scale items and data was collected from a total of 482 participants who were 3rd and 4th grade primary students. For construct validity, varimax orthagonal rotation connects with exploratory factor analysis was used. In the result of factor analysis, the scale involves in one factor explaining 42.46% of total variance. Based on the result of item analysis, the scale consisted of 33 items of which 29 were positive and 4 were negative. The overall Cronbachalpha coefficient of the scale was high (α= 0.94) indicating that it was a fairly consistent measure.The results of the study indicate that the scale named as primary school mathematics motivation scale (PSMMS) has good psychometric properties and is reliable and valid. It can be used reliably in future educational researches